Is vs30 a suitable parameter for site classification in seismic design code - Ker, Hanyi. (2009)
This report serves to explain the author’s work that has been done for the project. The report covers primary background research of the project topic, analysis tool, methodology of analysis, results and interpretations. Primary background research such as understanding earthquakes, its causes and its effects are crucial to completing the project by giving the author initial background knowledge of earthquakes. The report states the work done with regards to answering the main question of “is vs30 a good parameter for site classification in seismic design code?” The analysis in this project is carried out using EERA, a one-dimension earthquake analysis model. The project seeks to find results to either accept v30 as a suitable parameter or reject the claim. In the findings, it is established that vs30 is a suitable parameter in long term periods (T=1.0s), while in the short term (T=0.3s), vs30 may fail considerably as a suitable parameter in the seismic design.